Pour une approche interactionniste de la responsabilité sociale de l'entreprise : de la micro-RSE à l'entrepreneuriat de morale : le cas SNCF - Voiseux, Norélia (Université Paris 1, 2020)
Cette thèse porte sur la nature et les formes des interactions que la diffusion de la RSE va générer entre l’organisation (macro) et ses membres (micro), dans les contextes particuliers d’une entreprise publique ancrée à la société. Une approche interactionniste des phénomènes de micro-RSE nous a permis d’étudier les actions et les interactions des individus, et de comprendre ce qui leur permet de se connecter à l’organisation à travers différentes trajectoires de diffusion de la RSE. Nous mobilisons le cadre théorique de l’entrepreneuriat de morale pour analyser comment certains acteurs vont influencer la démarche de RSE, dans la façon dont elle va se diffuser et s’appliquer dans l’organisation et en dehors de ses murs.Nous nous appuyons sur sept portraits et trois cas d’étude « encastrés » à l’organisation. Les portraits dressés à partir de récits d’expérience de cheminot(e)s engagé(e)s dans la RSE, révèlent le rôle moteur de certaines valeurs morales venant faire écho aux particularismes culturels et moraux de l’entreprise publique.Les cas nous ont permis de caractériser différentes formes d’entrepreneuriat de morale dans des contextes où la moralité individuelle cherche à se (re)connecter avec celle de l’entreprise, notamment autour de certaines problématiques récentes (crise des migrants, érosion de la biodiversité), là où d’autres thématiques plus anciennes (comme l’économie circulaire) n’ont plus besoin de ce type de « campagne morale » pour s’imposer dans l’organisation. Une lecture par l’entrepreneuriat de morale permet d’enrichir le champ de la micro-RSE, notamment dans la compréhension des dynamiques bottom-up de ces phénomènes. This thesis focused on the nature and forms of interactions that the diffusion of CSR may generate between the organization (macro) and its members (micro), in the specific contexts of a public firm deeply rooted in the society. An interactionist approach to micro-CSR allowed us to study the actions and interactions of individuals, and to understand how they link to the organization through different ways of diffusion of CSR. We mobilize the theoretical framework of moral entrepreneur to analyse how some individual actors can influence the diffusion of CSR in and out the organization.We relied on a number of portraits and an embedded case study. Seven portraits were drawn from the experience stories of actors especially committed to CSR. They revealed the driving role of moral values which are specific to the culture and identity of public companies.Through three embedded cases, we characterized different forms of moral entrepreneurship when individuals seek to (re)connect their moral values with the company's ethical standards, especially around recent CSR issues (migrant crisis, biodiversity loss), while former issues (such as the circular economy) no longer need this type of “moral campaign” to prevail in the organization.The moral entrepreneurship framework can make a contribution to the field of micro-CSR, specifically in the top-down approach of these phenomena in organizational contexts.
Keywords: Ancrage social et territorial; Diffusion; Entrepreneuriat de morale; Entreprise publique; Entreprises publiques; France; Interactions micro-macro; Micro-CSR; Micro-RSE; Public company; Responsabilité sociétale; Société nationale des chemins de fer français; Éthique des affaires

La compétence universelle du juge en droit du travail - Delmas, Baptiste (Université de Bordeaux, 2020)
Le concept de compétence universelle est issu du droit international pénal. Il désigne l’habilitation des juridictions nationales répressives à connaître d’une affaire lorsque l’ensemble de ses éléments sont localisés dans un autre État que celui dont relève le juge saisi. En dépit d’une idée parfois véhiculée, la compétence universelle n’est pas l’apanage des crimes « les pires ». Elle est d’abord et avant tout une technique au service des juges nationaux afin de lutter contre l’impunité de certaines infractions. Son étude du point de vue du droit du travail se justifie par l’intérêt que peut susciter une telle technique pour les personnes travaillant pour le compte d’une entreprise transnationale ou d’une chaîne globale de valeur et pour lesquels il n’existe aucune garantie d’accéder à un juge en cas de violation de leurs droits au travail. En effet, ceux-ci sont exposés à un risque de déni de justice qui découle, d’une part, de l’inaptitude des tribunaux locaux à instruire un procès impliquant une entreprise dont le poids économique et politique dépasse celui de l’appareil judiciaire et, d’autre part, de l’incompétence de tout autre juge. Les dispositifs mis en place dans le cadre de la Responsabilité sociale des entreprises pas plus que les instruments régionaux de protection des droits de l’Homme garantissent à ces salariés l’accès à la justice. La compétence universelle du juge s’avère dont être une technique utile pour ces travailleurs. Mais c’est aussi une technique opérationnelle : non seulement ses éléments caractéristiques coïncident avec les difficultés d’accès à la justice des travailleurs dans un contexte de globalisation de l’économie mais, en plus, elle est déjà en voie d’apparition dans le contentieux social transnational.
Cotutelle : Université Laval
Keywords: CSR; Chaîne d’approvisionnement; Compétence universelle; Conflict of jurisdictions; Conflit de juridictions; Droit du travail; Droits fondamentaux; Entreprise transnationale; Fundamental rights; Globalisation de l’économie; Globalization of the economy; Juges; Labor law; Labour law; RSE; Responsabilité sociétale; Supply chain; Transnational companyghts; Universal jurisdiction

La négociation dans la régulation foncière-environnementale au Bénin - Korogone, Eloi Mere (Université de Limoges, 2020)
Le droit béninois du foncier et de l’environnemental ne fait pas consensus au niveau des communautés rurales à cause de l’exogénéité de ses référents juridiques. La fiction qui caractérise le droit positif, ne permet pas de répondre efficacement, aux besoins en normes des acteurs des diverses échelles de régulation foncière et environnementale. Les complexes juridiques à l’égard du droit du colonisateur et les préjugés défavorables sur l’endogénéité juridique, constituent des menaces potentielles à l’intérêt écologique national et à la sécurité foncière-environnementale des communautés rurales qui vivent exclusivement de l’agriculture familiale. Face à l’urgence écologique déclarée, aux changements climatiques et à l’insécurité foncière qui sévissent dans les aires protégées et les patrimoines fonciers communs, il faut donner une nouvelle perspective juridique du rapport à la terre et aux éléments biotiques qu’elle supporte. L’enjeu du droit positif béninois se situe sur deux plans : a) la prise en comptes des pratiques, des coutumes et des habitus locaux, dans la mesure de leur juridicité prouvée, qui permet d’asseoir le droit de l’Etat dans son contexte socio-culturel et économique et d’assurer son efficacité dans la gouvernance des ressources foncières et environnementales ; b) la mise en place des mécanismes transparents de règlement des conflits fonciers ruraux et le développement des mécanismes permettant de sortir les arrangements sociaux de l’oralité pour plus de formalisme et une coviabilité socio-écologique. La coviabilité socio-écologique dépend de la capacité du pays à opérer une jonction entre l’endogénéité juridique et le droit de l’Etat. Et seule, la négociation dans la régulation foncière-environnementale permet de tendre vers cette perspective juridique pragmatique à travers une approche socio-anthropologique du droit négocié. There is no consensus on Beninese land and environmental law at the level of rural communities because of the exogeneity of its legal referents. The fiction that characterizes positive law does not make it possible to respond effectively to the needs for standards of actors at the various levels of land and environmental regulation. The legal complexes with regard to the law of the colonizer and the unfavourable prejudices on legal endogeneity constitute potential threats to the national ecological interest and to the land tenure-environmental security of rural communities that live exclusively from family farming. In the face of the declared ecological emergency, climate change and the insecurity of land tenure in protected areas and common land heritages, a new legal perspective must be given to the relationship to land and the biotic elements it supports. The challenge for Beninese positive law is twofold: (a) taking account of local practices, customs and habits, insofar as their legality has been proven, which makes it possible to establish State law in its socio-cultural and economic context and to ensure its effectiveness in the governance of land and environmental resources; (b) the establishment of transparent mechanisms for the settlement of rural land conflicts and the development of mechanisms to take social arrangements out of orality for more formalism and socio-ecological coviability. Socio-ecological coviability depends on the country's ability to bridge the gap between legal endogeneity and State law. And only negotiation in land tenure-environmental regulation makes it possible to move towards this pragmatic legal perspective through a socio-anthropological approach to negotiated law.
Keywords: Coviabilité socio-écologique; Endogénéité juridique; Land tenure-environmental regulation; Legal endogeneity; Propriété foncière; Régulation foncière-environnementale; Socio-ecological coviability

Commercialization of Microfinance in Cameroon : How can Microfinance Institutions manage their dual social and commercial goals? - Singhe, Steffi Sandra (Université de Nantes, 2020)
La commercialisation de la microfinance a mis au premier plan la performance financière des I MF, les IMF adoptant désormais une logique commerciale de rentabilité en plus de leur logique sociale établie de lutte contre la pauvreté. Cela pose un défi de gestion crucial pour les IMF pour équilibrer l'aspect social et commercial de leur mission. Cette thèse vise à analyser comment les IMF surmontent leurs défis pour atteindre leur double objectif social et commercial. Elle s'appuie sur le concept de bricolage comme perspective théorique et sur une approche méthodologique abductive, exploratoire et qualitative. La thèse vise également à fournir une meilleure compréhension du secteur de la microfinance camerounaise, en termes de son histoire et évolution, et des défis spécifiques au secteur. L'étude identifie diverses pratiques de bricolage que les IMF utilisent pour faire avancer la réalisation de leur double mission. Les résultats suggèrent l'utilisation de ces pratiques de bricolage par les IMF pour mobiliser des ressources, renforcer la légitimité et accroître leur ou/reach, dans un contexte caractérisé par des contraintes de ressources. Ces trois résultats de bricolage se renforcent mutuellement pour faciliter la réalisation du double objectif des IMF. Cette recherche a également mis en évidence les quatre phases d'évolution du secteur de la microfinance camerounaise et les cinq principaux défis auxquels sont confrontées les IMF du secteur. Cette thèse contribue à la littérature sur la microfinance. Elle propose un nouvel regard sur la gestion de la double mission des IMF en montrant comment les IMF mobilisent les stratégies de bricolage pour faire avancer leurs objectifs sociaux et commerciaux. Elle met en lumière le lien entre la littérature sur la microfinance et le bricolage. The commercialization of microfinance has brought to the forefront the financial performance of MF!s, with MF!s now adopting a commercial logic of profitability in addition to their established social logic of poverty alleviation. This poses a crucial management challenge for the MF!s in terms of balancing the social and commercial aspect of their mission. The main aim of this thesis is to understand how MFls overcome their challenges so as to achieve their dual social and commercial goals. lt draws on the bricolage concept as a theoretical perspective and on an abductive, exploratory and qualitative research approach. The thesis also aimed to provide a better understanding of the Cameroonian microfinance sector, in terms of its history and evolution, and the challenges specific to the sector. The study identifies various bricolage practices that the MF!s use to advance the fulfilment of their dual mission. The findings suggest the use of these bricolage practices by the MF!s to mobilize resources, build legitimacy, and increase outreach, in a context characterized by resource constraints. These three bricolage outcomes reinforce each other, and they all strengthen the achievement of the MF!s' dual goals. This research also highlighted the four phases of evolution of the Cameroonian microfinance sector and the five main challenges faced by MF!s in the sector. This thesis contributes to the microfinance literature. lt offers a new perspective on MF! dual-mission management by showing how MF!s mobilize bricolage practices to advance their dual social and commercial goals. lt brings light on the link between the literature on microfinance and bricolage.
Keywords: CSR; Cameroun; Microfinance; RSE; Responsabilité sociétale; Régulation (théorie)

Relationship between corporate social responsibility practice and its effects on the botton-line - Tandoh, Isaac; Aovare, Ayishetu (International Journal of Innovation and Scientific Research, 2020)
The study comparatively evaluates the relationship between Corporate Social Responsibility and Profitability in the fuel and gas sectors in Ghana. The descriptive survey design and quantitative methods was adopted to find a relationship between innovations in strategic stakeholder engagement with corporate profitability or bottom-line, with the mediating role of strategic stakeholder engagement leading to a firm’s bottom-line. An analysis of strategic stakeholder engagement and bottom-line of selected fuel and gas companies in the Kumasi Metropolitan, Asokore Mampong, Oforikrom and Ejisu Municipalities was provided.A five point closed ended Likert Scale self-administrable structured questionnaire and researcher guide to aid participants answer relevant questions was used to confirm that innovations in strategic stakeholder engagement fueled increases in corporate bottom-line of selected companies. The four major steps of analysing data collected from Atkinson’s (2002) categories of quantitative data analysis was used, following which the primary data/information gathered and coded was analysed using the Statistical Package for Social Sciences to guarantee validity and reliability of the various investigations conducted. The hierarchical multiple regression of the Baron and Kenny’s (1986) procedure was also adopted to analyse for study the mediating effect of innovation on the relationship between strategic stakeholder engagement and corporate bottom-line.The study opines the involvement of key stakeholder participation in the siting and general operations of fuel and gas companies given the divergent viewpoints of operators and stakeholders (O’Riordan, 2017). A discovery of a statistically significant positive influence of perceptions of CSR towards customers on an organization’s image in general intensifies the suggestion that mangers of fuel and gas sectors take special interest in innovative ways of engaging strategic stakeholders due to its influence and ripple mediating effect on corporate bottom-line to improve the performance of the business or induces increases in profit.
Keywords: Brand; Corporate Social Responsibility; Employees; Image; Perception; Strategic Stakeholder

The Impact of Employee Board Representation on the Firm’s CSR Engagement : evidence from the French Context - Boukadhaba, Amal (Le Mans Université, 2020)
Cette thèse propose d’examiner la relation entre la représentation des salariés dans le conseil d’administration et l’engagement RSE de l’entreprise. En particulier, nous étudions comment les investisseurs perçoivent-ils le reporting RSE et laperformance ESG lorsque les salariés sont représentés au sein du conseil d’administration. En utilisant un échantillon de sociétés françaises appartenant à l’indice SBF 120 sur deux périodesdifférentes de 2001 à 2011 et de 2007 à 2017, nos résultats montrent que la présence des administrateurs salariés modère positivement la perception du reporting RSE et négativement la perception de la performance ESG par les investisseurs. Un examin plus détaillé montre que les administrateurs élus par les salariés par leur droit de travail améliorent exclusivement la performance sociale et modèrent négativement la perception des investisseurs vis-à-vis de la performance ESG. Au contraire, les administrateurs élus par les salariés actionnaires renforcent la performance ESG globale ainsi que les performances environnementale et de gouvernance et modèrent positivement la perception de la performance ESG par les investisseurs. Nos résultats mettent en évidence un conflit d’intérêts entre les actionnaires et les administrateurs salariés, notamment avec les représentants des travailleurs. Cette thèse couvre plusieurs disciplines à savoir la comptabilité, la gouvernance d’entreprise et lagestion des ressources humaines. En conséquence, elle intérèsse vivement les législateurs, les investisseurs, les managers et les actionnaires.
Impact de la représentation des salariés au sein du conseil d’administration sur l’engagement RSE de l’entreprise : Etude du contexte français
Keywords: Actionnariat du personnel; Administrateurs salariés; CSR reporting; ESG performance; Employee board representation; Firm market value; Gouvernement d'entreprise; Performance ESG; Performance boursière; Personnel – Participation à la gestion; Relations avec les actionnaires; Reporting RSE; Responsabilité environnementale; Responsabilité sociétale; Sociétés

La responsabilité sociale de l'entreprise - Cardoso, Carla (Institut National Universitaire Champollion, 2020)
La prise de conscience mondiale de la nécessité de promouvoir les nouveaux enjeux sociétaux et environnementaux a permis le renouveau du concept ancien connu sous l’expression de Responsabilité Sociale des Entreprises. Sujet se développant au gré des changements sociaux et de l’évolution des mœurs, l’étude de la RSE dans le cadre de ce mémoire a été appréhendée sur un double plan : notionnel par la délimitation du concept flou qu’elle représente puis juridictionnel par l’étude du régime et des règles en découlant. Dans un premier temps, il s’agit d’appréhender la définition qu’il est possible de retenir de la notion, de comprendre son étendue et les acteurs concernés par sa mise en place dans les entreprises. Dans un second temps, il faut étudier le régime juridique applicable à la RSE au travers de la cohabitation existante entre les règles de soft law dites non contraignantes et celles de hard law, c’est-à-dire coercitives. Le fil conducteur de cette étude est en effet de comprendre quels sont les enjeux sociaux et environnementaux existants à la mise en œuvre d’une Responsabilité sociale dans les entreprises aux différentes étapes de sa vie : création, gestion et restructuration. Se pose assez logiquement la question de savoir si les normes issues du concept de RSE ont un impact véritable sur les comportements et agissements des entreprises.
Keywords: Droit de l'environnement; Droit des affaires; Droit du travail; Développement durable; Entreprise; Hard law; Labour law; Parties prenantes; Responsabilité; Responsabilité Sociale de l'Entreprise; Soft law

Corporate Social Responsibility and Organizational Performance of Oil Companies in Southern Nigeria - Daubry, Powei Martin (Walden University, 2020)
In this study, the relationship between corporate social responsibility (CSR) activities and organizational performance (OP) of international oil companies (IOCs) operating within the Niger Delta Region of Nigeria was investigated. Grounded on the stakeholder theory, the problem being investigated involved the extent to which dimensions of CSR in terms of centrality, visibility, and voluntary contributions impact measures of OP (relational capital and employees’ commitment) specifically within the oil industry in Nigeria. Data for the study were obtained through a quantitative survey instrument from a sample of a population of individuals (N=270) living in host communities who are impacted by IOC activities in Rivers, Delta, and Bayelsa States. The results of the multiple regression analysis indicated a predictive model F (1, 268) = 774, p < 0.05, and R 2 = .742, which indicated that CSR was positively and significantly correlated with OP. In addition, centrality and voluntary contributions significantly affected OP. Also, centrality and voluntary contributions significantly correlated with employees’ commitment while only voluntary contributions significantly correlated with relational capital. The results of the study corroborated the need for CSR practitioners in the oil industry within the Niger Delta to operate in a socially responsible manner. The implications for positive social change include the potential for policy makers to use the findings to create mutually beneficial relationships that could contribute to resolving persistent adverse issues involving oil exploration and production in the Niger Delta Region by improving the socioeconomic dynamics of the host population, not only in the region, but also throughout Nigeria and similar countries.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Oil companies; Organizational performance

Şirketlerin insan hakları sorumluluğuna hak temelli bir yaklaşım: İnsan hakları due diligence'i (Human right due diligence) - Çimrin Ardiç, Çiğdem (İstanbul Bilgi Üniversitesi, 2020)
Çokuluslu şirketlerin etki alanı küresel olmakla birlikte, gerçekleştirdikleri faaliyetlerdeki menfaatleri özeldir ve nihai hedefleri de kârlılıklarını arttırmaktır. 1970'lerden itibaren çokuluslu şirketlerin dünyanın ekonomik kalkınmasına hizmet edebileceğine yönelik toplumsal beklentinin gerçekçi olmadığı ciddi insani ve çevresel maliyetleriyle birlikte anlaşılmıştır. Gerçekten de, neoliberal politikalar, ekonomik küreselleşme ve uluslararası yatırım antlaşmaları rejimiyle daha da güç ve nüfuz kazanan çokuluslu şirketlerin sebep olduğu siyasi, ekonomik, hukuki, çevresel ve sosyal sorunlar günümüzde belirgin bir hale gelmiştir. Toplumsal ve küresel eşitsizliklerin ve adaletsizliklerin daha da derinleşmesi kamuoyunda büyük endişe yaratmaktadır. Yaşanmakta olan bu süreç, insan haklarını koruma ve mağduriyetleri telafi mekanizmalarının yetersizliklerini gözler önüne sermektedir. Çokuluslu şirketlerin faaliyetlerini nasıl gerçekleştirdiğine veya güçlerini ne yönde kullandıklarına ilişkin hesap verilebilirliğin sağlanabilmesi için ortaya çıkan toplumsal beklentinin karşılanabilmesi amacıyla, 2011 yılında Birleşmiş Milletler İnsan Hakları Konseyi tarafından oybirliğiyle kabul edilen Rehber İlkeler çerçevesinde, devletlerin insan haklarını koruma ödevlerinin yanı sıra şirketlerin de insan haklarına saygı gösterme sorumluluğunun olduğu ve bu sorumluluğun gereklerini yerine getirmek için insan hakları etki incelemesi (HRDD) yapmaları gerektiği açık bir şekilde ifade edilmiştir. Şirketlere atfedilen bu insan hakları sorumluluğunun uluslararası hukukta ve uluslararası insan hakları hukukunda temellendirilmesi önem taşımaktadır. Zira, çokuluslu şirketlerin tedarik zincirlerindeki uygulamaları, uluslararası hukukun emredici kurallarının (jus cogens) ihlallerini de içeren birçok insan hakları ihlallerine sebebiyet vermektedir. Ancak, iç hukuk sistemlerinde çokuluslu şirketlerin örgütlenme biçimleri ve tüzel kişilik perdesinden kaynaklanan kısıtlar nedeniyle hesap verilebilirlikleri sağlanamamaktadır. Gerçekten de, iş dünyası ve insan hakları alanının esas tartışması ve sermayenin insan hakları ihlalleri kaynaklı yaşanan adaletsizliklerin esas nedeni, çokuluslu şirketlerin insan hakları sorumluluğunun sağlanabilmesine karşı en başta ticaret hukuku ve sözleşmeler hukuku olmak üzere iç hukukta yer alan yasal engeller, liberalizmin kalıplaşmış bakış açılarının aşılamaması ve çokuluslu sermayenin (yabancı yatırımın) ekonomik kalkınmayı ve toplumsal gönenci beraberinde getireceğine yönelik gerçekdışı beklentidir. Şirketlerin sahip olduğu insan hakları sorumluluğu uluslararası örf ve âdet hukuk normu olarak belirdikten sonra Rehber İlkeler kapsamında beyan edilmiş, HRDD de bu sorumluluğunun gereklerini ifa edilebilmesi için önemli ve gerekli bir risk tespit aracı olarak öngörülmüştür. Devletlerin insan haklarını koruma ödevleri gereği, şirketlerden hesap sorulabilirliğin ve hak mağdurlarının adalete erişimlerinin sağlanabilmesi için iç hukuk engellerini kaldırması ve/veya hesap sorulabilirliği kolaylaştırıcı iç hukuk düzenlemeleri yapması gerekmektedir. Son dönemde özellikle Avrupa Birliğinde ve Avrupa Birliğine üye olan devletlerde yaşanan yasal gelişmeler de bu gerekliliğin bir sonucudur. Even though the domain of multinational companies is global, their interests are private and their ultimate goal is to increase their profitability. Since 1970s, it has been understood that the social expectation that multinational companies can serve for the economic development of the world is not realistic and this understanding was gained with serious human and environmental costs. Indeed, the political, economic, legal, environmental and social problems caused by the mutinational companies, who have assumed more power and influence through widespread neoliberal policies, economic globalization and international investment treaties regime, have become more evident today. The intensification of social and global inequalities as well as injustice among societies raised great concern in the public opinion. This ongoing process reveals the shortcomings and inadequacies of human rights protection and remediation mechanisms. In order to meet the social expectation for ensuring legal accountability of multinational companies regarding their global activities, in 2011 the United Nations Human Rights Council unanimously adopted the 'Guiding Principles on Business and Human Rights', which explicity sets forth corporate responsibility to respect human rights in addition to already existing state duty to protect human rights. Guiding Principles also states that business actors should make human rights due diligence (HRDD) to fulfill the requirements and conditions of their human rights responsibility. It is important to establish legal basis of corporate responsibility to respect human rights within the scope of international law and international human rights law. Otherwise, such responsibility would not be legally enforceable and thus, one can easily argue that this responsibility exists in vacuum juris. However, we have been witnessing various practices and operations of multinational companies within their supply chains, which would constitute human rights violations - in fact, some of these violations are breaches of jus cogens. Nonetheless, it is not possible to ensure the legal accountability of multinational companies in the current national legal systems due to legal barriers arising from how multinational companies' organizations are structured and corporate veil doctrine stipulated in national laws. The main discussion in the field of business and human rights and the main reason for injustices due to human rights violations by corporate actors; legal barriers arising from domestic law – particularly, commercial and contractual law – for establishing human rights responsibility of multinational companies, inability to go beyond streotypical approach of liberalism, and the unrealistic expectation that multinational companies (as well as foreign investment) will bring economic development and social welfare. As a matter of fact, the corporate responsibility to respect human rights has been declared within the scope of the Guiding Principles after this responsibility was emerged as an international customary law norm. HRDD is also envisaged as an important and necessary risk assessment tool for the fulfillment of this responsibility's requirements. As precribed by the duty of states to protect human rights, in order to ensure legal accountability of corporate actors and to enable victims' access to justice, removing domestic legal barriers and enacting necessary regulations that would facilitate accountability are required. Recent legal developments, especially in the European Union and the member states of the European Union, are also a result of this necessity.
Keywords: Business world; Companies; Due diligence; Fundamental rights; Guiding principles; Human rights; Rehber ilkeler; Social rights; Sosyal haklar; Temel haklar; Özen yükümlülüğü; İnsan hakları; İş dünyası; Şirketler

Corporate social responsibility and executive personality - Li, Xin (Simon Fraser University, 2020)
My dissertation investigates two streams of managerial accounting literature; specifically, corporate social responsibility (CSR) and executive personality. Paper 1 focuses on whether companies strategically engage in CSR practices to retain employees. Using a difference-in-differences design, I find that an increase in the enforcement of non compete agreements (which enhances a firm’s ability to retain employees) deteriorates CSR performance. Paper 2 extends prior literature and links managerial risk tolerance and firms’ CSR performance. The empirical result of Paper 2 shows that pilot CEOs are less likely to exhibit better CSR performance. Paper 3 examines the spillover effect of managerial risk tolerance along the supply chain. Specifically, I follow Paper 2 to use the pilot status of CEOs to proxy for the customers’ risk tolerance level. Overall, the results support a negative association between customer risk tolerance and supplier investment efficiency, and customer companies ran by pilot CEOs leads to supplier investment inefficiency. Each chapter is designed to be self-contained and provides a more detailed discussion of the research question and contribution.
Keywords: CEO; CSR performance; Corporate Social Responsibility; Non-compete enforceability; Pilot; RSE; Risk tolerance; Supplier investment efficiency

The Trajectory of Illicit Waste Trade in Africa: Implications for Human Rights and Sustainable Development - Umenze, Nnamdi Stanislaus (Journal of Law, Society and Development, 2020)
As globalisation intensifies, the environmental burden of economic development is being shifted to poor countries. This development manifests in waste trade involving the transboundary shipment of toxic waste from developed to developing countries. This article evaluates the strategies with which waste trade is being perpetuated to the detriment of sustainable development and human rights values in Sub-Sahara Africa. It argues that capitalism has influenced massive generation and commodification of waste, especially in industrialised countries. It has also established that globalisation has made the transboundary shipment of waste easy. Moreover, foreign investments in the waste industry in developing countries appear to be a means by developed countries to perpetuate waste shipment to developing countries, which helps waste traders to avoid stringent regulations and high costs of waste management in developed countries. Therefore, such investments in developing countries should not always be viewed as a breakthrough in attracting foreign investments. The findings made include that despite the existence of the Basel and Bamako Conventions at global and regional levels, respectively, waste trade has continued in different forms in Africa, where waste merchants exploit the low-cost facilities, cheap labour and weak regulatory frameworks. The trend includes the reckless dumping of hazardous industrial waste, electronic waste as well as ostensible investment in “dirty industries” in some African countries. It concludes by urging the states to individually establish robust mechanisms that protect the environment and enforce environmental rights. These measures will help complement the collective efforts they have made in multilateral and regional agreements.
Keywords: Africa; electronic waste; globalisation; human rights; sustainable development; toxic waste trade